Cortical Source Estimate of Combined High Resolution EEG and fMRI Data Related to Voluntary Movements - Babiloni, F.; Babiloni, C.; Carducci, F.; Gratta, Del C.; Romani, G. L.; Rossini, P. M.; Cincotti, F. (Methods of Information in Medicine, 2002)
Objectives: In this paper, we employed advanced methods for the modeling of human cortical activity related to voluntary right one-digit movements from combined high-resolution electroencephalography (EEG) and functional magnetic resonance imaging (fMRI).Methods: Multimodal integration between EEG and fMRI data was performed by using realistic head models, a large number of scalp electrodes (128) and the estimation of current density strengths by linear inverse estimation.Results: Increasing of spatial details of the estimated cortical density distributions has been detected by using the proposed integration method with respect to the estimation using EEG data alone.Conclusion: The proposed method of multimodal EEG-fMRI data is useful to increase spatial resolution of movement-related potentials and can also be applied to other kinds of event-related potentials.
Keywords: High resolution EEG; fMRI; multimodal integration of EEG and fMRI; voluntary movements; event-related fMRI